2002
DOI: 10.1172/jci16588
|View full text |Cite
|
Sign up to set email alerts
|

Induction of the Cdk inhibitor p21 by LY83583 inhibits tumor cell proliferation in a p53-independent manner

Abstract: Conflict of interest:The authors have declared that no conflict of interest exists. Nonstandard abbreviations used: human diploid fibroblast (HDF); 6-anilino-5,8-quinolinequinone (LY83583); LY83583 (LY); mouse embryo fibroblasts (MEFs); elongation factor 1α (ELF1α); soluble guanylate cyclase β3 (sGC-β3); quantitative real-time PCR (qPCR); crossing point (CP); propidium iodide (PI); sodium nitroprusside (SNP); senescence-associated β-galactosidase (SA-β-gal); bromodeoxyuridine (BrdU); soluble guanylate cyclase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 45 publications
2
20
0
Order By: Relevance
“…However, P21, cyclin-dependent inhibitor (CKI), has been suggested to lead to the G1 arrest and proliferation inhibition of breast cancer cells. 25 In our study, P21 was found to be upregulated for CA treatment in both two liver cancer cell lines, which was consistent with a previous study 26 ( Figure 8C and D). And conversely, Cyclin-D1 and Cyclin-D3, as two essential regulators for cell cycle, were also determined.…”
Section: The Effect Of Ca On Nf-κb Pathway In Akt-deficient Liver Cansupporting
confidence: 93%
“…However, P21, cyclin-dependent inhibitor (CKI), has been suggested to lead to the G1 arrest and proliferation inhibition of breast cancer cells. 25 In our study, P21 was found to be upregulated for CA treatment in both two liver cancer cell lines, which was consistent with a previous study 26 ( Figure 8C and D). And conversely, Cyclin-D1 and Cyclin-D3, as two essential regulators for cell cycle, were also determined.…”
Section: The Effect Of Ca On Nf-κb Pathway In Akt-deficient Liver Cansupporting
confidence: 93%
“…RNA was converted to biotinylated cRNA and hybridized to oligonucleotide arrays representing B22 000 individual transcripts. A large number of genes were found to be induced after treatment with 5Aza-2 0 dC plus TSA vs TSA alone (Lodygin et al, 2002). GSTP1, a gene known to be hypermethylated in the majority of PCa (Singal et al, 2001), was induced 1.87-fold in LNCaP cells after combined treatment with 5Aza-2 0 dC and TSA.…”
Section: Resultsmentioning
confidence: 99%
“…At the indicated time points, cells (both adherent and floating) were harvested by trypsinization, washed once with PBS and fixed in 70% ethanol for 2 h on ice, washed once with PBS and incubated for 30 min at room temperature in PBS solution containing 50 mg/ml propidium iodide, 0.2 mg/ml RNase A and 0.1% Triton X-100 v/v (Lodygin et al, 2002). For each sample, 10 000 events were analysed with a FACScan unit (Becton Dickinson).…”
Section: Dna Content Analysis By Flow Cytometrymentioning
confidence: 99%
“…Western blotting analysis was done as described previously (15). Antibodies used were directed against a-tubulin (Santa Cruz), vesicular stomatitis virus (Sigma), and phospho-ERK1/2 and ERK1/2 (Cell Signaling Technology, Frankfurt, Germany).…”
Section: Methodsmentioning
confidence: 99%